Intolerance of uncertainty and attitudes towards persons living with disabilities in medical students: Is there a correlation? - Martinique Ogle; Dimitrios Papanagnou; Kestrel Reopelle; Frances Rusnack; Jordan Feingold-Link; Maria Poluch; Nethra Ankam (Frontiers Media S.A., 2023)
IntroductionPatients living with a disability experience an illness trajectory that may be uncertain. While navigating clinical uncertainty has been well-researched, health professionals' intolerance of uncertainty for patients living with disabilities has yet to be explored. We examined the relationship between medical students' intolerance of uncertainty with their attitudes towards people living with disabilities to better inform curricular efforts.MethodsWe employed a survey-based design consisting of the Intolerance of Uncertainty Scale (IUS) and Disability Attitudes in Healthcare (DAHC) Scale to medical students upon completion of core clerkships (end of third-year of training). Data were de-identified. Mean DAHC and IUS scores were compared with published values via t-test. Linear regression was used to examine IUS/DAHC scores for anonymized students. Pearson correlation coefficient was calculated to assess correlation between IUS and DAHC scores.ResultsResponse rate was 97% (268/275 students). Mean IUS score did not differ from previously cited medical student scores, but mean DAHC score was significantly higher than previously cited scores. We observed a statistically-significant relationship between IUS and DAHC scores. Students with greater intolerance of uncertainty had lower scores for disability attitudes [F(1,243) = 8.05, value of p < 0.01], with an R2-value of 0.032, suggesting that 3% of DAHC score variance can be explained by IUS score changes.ConclusionWe identified a weak negative correlation between IUS and DAHC scores in medical students. Further research is needed to clarify findings and identify best practices that equip trainees with skills to care for patients with uncertain illness trajectories and patients living with disabilities.